Literacy Training of Halal Food for SMEs as the Opportunity to Penetrate the Global Market - Wibowo, Mas Wahyu; Indrajaya, Sonny; Permana, Dudi (Jurnal Abdi Masyarakat (JAM), 2023)
Halal food has become the global phenomenon, where the demand of the product are rising due to the growth of Muslim consumers worldwide. Halal food also perceived beyond its basic function where the consumers consider the product to fulfill their halal lifestyle. During the sperad of Corona-19 virus, halal food economic performance remains the strongest amongst the other sector within the halal industry. In this regard, the current community service aims to provide literacy to the SMEs related to the potential of halal food business during the pandemic era. Further, the Indonesian halal certification body has recognized by more than 50 international halal certification bodies. Therefore, SMEs has the opportunity to penetrate the global market with halal food.